Chemical, biological, and functional aspects of food lipids - Sikorski, Zdzisław E.; Kołakowska, Anna, 1938- (Chemical and functional properties of food components series., 2011)
"Chemical, Biological, and Functional Aspects of Food Lipids provides a concise, straightforward treatment of the present state of knowledge of the nomenclature, content, composition, occurrence, distribution, chemical and biological reactivity, functional properties, and biological role of lipids in food systems. Written by a team of international researchers and based on the available world literature, this book examines the nature, technological properties, reactivity, and health-related concerns and benefits of food lipids. It covers the effects of storage and processing conditions on all aspects of quality of lipid-containing foods and reviews the current state of techniques for lipid analysis. The volume also discusses the importance of lipids in the human diet and includes a comparison of dietary recommendations for lipid intake. This is a valuable reference for researchers and graduate students in food chemistry and nutrition"--